USE OF PEDAGOGICAL SITUATIONS ON FOREIGN LANGUAGE CLASSES IN HIGHER EDUCATION - Zorenko, I.S. (Pedagogy of Higher and Secondary Education, 2022)
The article studies the notion of "pedagogical situation". It presents the types of pedagogical situations at foreign language lessons.